Intraoperative mapping of the right hemisphere: a systematic review of protocols that evaluate cognitive and social cognitive functions - Martín-Monzón, Isabel; Amores-Carrera, Laura; Sabsevitz, David; Herbet, Guillaume (Frontiers in Psychology, 2024)
The right hemisphere of the brain is often referred to as the non-dominant hemisphere. Though this is meant to highlight the specialized role of the left hemisphere in language, the use of this term runs the risk of oversimplifying or minimizing the essential functions of the right hemisphere. There is accumulating evidence from functional MRI, clinical lesion studies, and intraoperative mapping data that implicate the right hemisphere in a diverse array of cognitive functions, including visuospatial functions, attentional processes, and social cognitive functions. Neuropsychological deficits following right hemisphere resections are well-documented, but there is a general paucity of literature focusing on how to best map these functions during awake brain surgery to minimize such deficits. To address this gap in the literature, a systematic review was conducted to examine the cognitive and emotional processes associated with the right hemisphere and the neuropsychological tasks frequently used for mapping the right hemisphere during awake brain tumor surgery. It was found that the most employed tests to assess language and speech functions in patients with lesions in the right cerebral hemisphere were the naming task and the Pyramids and Palm Trees Test (PPTT). Spatial cognition was typically evaluated using the line bisection task, while social cognition was assessed through the Reading the Mind in the Eyes (RME) test. Dual-tasking and the movement of the upper and lower limbs were the most frequently used methods to evaluate motor/sensory functions. Executive functions were typically assessed using the N-back test and Stroop test. To the best of our knowledge, this is the first comprehensive review to help provide guidance on the cognitive functions most at risk and methods to map such functions during right awake brain surgery. Systematic Review Registration PROSPERO database [CRD42023483324].